If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7v-26=-2(v-5)
We move all terms to the left:
7v-26-(-2(v-5))=0
We calculate terms in parentheses: -(-2(v-5)), so:We get rid of parentheses
-2(v-5)
We multiply parentheses
-2v+10
Back to the equation:
-(-2v+10)
7v+2v-10-26=0
We add all the numbers together, and all the variables
9v-36=0
We move all terms containing v to the left, all other terms to the right
9v=36
v=36/9
v=4
| 30x+5=32x-3 | | x/3+9=23 | | -6m-1=7m-1 | | 3z+2.19=-3.33 | | C(x)=40.00-0.05x | | 31x+1=30x+4 | | -28-3n=4(7+8)-n | | 9x+23=5x-11 | | 16y+49=193 | | 5x+0.7=45.7 | | -3(x-3+2=-1) | | b/7+21=3 | | 52+20f=572 | | N/4=x+5(3)=27 | | 19x=18x+15 | | 3=2n | | 17x-6=5x+10 | | 3x+4+5x+6=38 | | 6+4x+2=7x+2 | | 17x+2=26x+6 | | 63+-14w=-721 | | 5/36y=5/12 | | -n+-25=-58 | | 4=3x-20/2 | | -5n+-215=500 | | 5÷36y=5÷12 | | -1/3m+3/5=-3/5 | | x+15+2x+18=12 | | c/2-3.1=-0.1 | | z/12-4=7 | | 118-3s=76 | | 8*g=-38 |